Simplified approach for the optimal number of rotors and support structure design of a multi rotor wind turbine system - Sven Störtenbecker; Rudolf Anselm; Peter Dalhoff (Journal of physics, 2020)
In this study different multi rotor wind turbine systems (MRSs) are designed in such a way that the space frame, forming the connection between rotor nacelle assemblies (RNAs) and tower, will be modeled and dimensioned as an ideal truss work. The main focus is on multi digit MRSs (MD-MRS) with a high number of rotors. To dimension the tube diameters and wall thicknesses, a simplified load case is used with an adjusted safety factor for loads. Parameters that are varied are the number of rotors, depth of the space frame, as well as the location of the fixed bearing for the yaw system. As such, the simplified approach is a preliminary step helping to choose a good design parameter combination for a more detailed and comprehensive analysis. Buckling is a main design driver, as well as the thrust forces. For a high number of rotors, a fixed bearing position and therefore tower height, halfway through the space frame height seems favorable regarding the cost (CC BY 3.0, Attribution 3.0 licence).
Keywords: Windenergie; Multirotor; wind energy; multi-rotor